66.0k views
0 votes
DO IT ASAP! Thank you very much!

DO IT ASAP! Thank you very much!-example-1
User Medo
by
5.2k points

1 Answer

6 votes

Answer:

a = 5

Explanation:

According to the factor theorem, if x + 2 is a factor, then by dividing the polynomial by the binomial, we are meant not to have a remainder

In this case, the remainder would be zero

So, if we set the binomial equals zero and substitute the x-value into the polynomial, we are supposed to have 0

So we have this as;

x + 2 = 0

x = -2

-2^3 -2(-2)^2 -2(a) + 6 = 0

-8-8-2a + 6 = 0

-16 + 2a + 6 = 0

2a -10 = 0

2a = 10

a = 10/2

a = 5

User Parakh
by
5.1k points